Penentuan kalsium susu kambing segar dengan Spektrofotometri Serapan Atom (SSA) - Safrina Safrina; Azmalina Adriani; Eva Novita (Poltekkes Kemenkes Aceh, 2026)
Background: Calcium (Ca) is an essential mineral abundantly present in goat milk and plays a crucial role in bone and dental development. Data on Ca levels in local goat milk from Banda Aceh remain limited, although such information is important for nutritional purposes and the development of livestock products. Atomic absorption spectrophotometry (AAS) is employed for mineral analysis owing to its high sensitivity and selectivity.Objective: This study aimed to determine the calcium content in fresh goat milk from three locations in Banda Aceh and Aceh Besar and to evaluate any differences between them.Methods: This was a descriptive quantitative research with an experimental laboratory approach conducted in Banda Aceh in 2025. Fresh goat milk samples were collected from Gampong Tibang (GT), Gampong Kopelma Darussalam (KD), and Gampong Lamblang Manyang (LM) in April 2025. The samples were digested with concentrated HNO₃ and analyzed using AAS at 422.7 nm. Data were statistically analyzed using one-way ANOVA.Results: The highest calcium content was found in KD (0.892 mg/L), followed by GT (0.856 mg/L), and the lowest in LM (0.582 mg/L). The overall mean calcium level was 0.777 mg/L. One-way ANOVA confirmed significant differences among locations (F = 61.62; p = 0.0001). Conclusion: Calcium levels in fresh goat milk varied significantly among locations and were potentially influenced by environmental factors, feeding practices, and goat physiology. These findings are expected to serve as a basis for developing high-quality local goat milk products and supporting the utilization of functional foods.